2015
DOI: 10.1002/lary.25439
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a rigid esophagoscopy simulator for residency training

Abstract: NA Laryngoscope, 126:616-619, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…96 In a subsequent study, 97 the authors found that resident technical skills improved and repeated procedures were safer. Similarly, simulations in drainage of peritonsillar abscesses, 85 laryngeal injections, 88 esophagoscopy, 109 bronchoesophagoscopy, 28 complex mandibular reconstruction, 90 and assessment of a foreign body in the pedi-atric airway 13 were created to assess resident technical skills and knowledge. In each study, the simulations were found to be reliable instruments for assessment.…”
Section: Medical Knowledgementioning
confidence: 99%
“…96 In a subsequent study, 97 the authors found that resident technical skills improved and repeated procedures were safer. Similarly, simulations in drainage of peritonsillar abscesses, 85 laryngeal injections, 88 esophagoscopy, 109 bronchoesophagoscopy, 28 complex mandibular reconstruction, 90 and assessment of a foreign body in the pedi-atric airway 13 were created to assess resident technical skills and knowledge. In each study, the simulations were found to be reliable instruments for assessment.…”
Section: Medical Knowledgementioning
confidence: 99%
“…Greater efforts have been made to develop and incorporate surgical simulation models into OHNS training curricula . However, the tangible benefits associated with these models has remained uninvestigated.…”
Section: Discussionmentioning
confidence: 99%
“…Many additional examples of using simulation or educational tools for resident learning have had positive results. Allak et al 11 developed a simulator for performing rigid esophagoscopy. Otolaryngology residents with varied levels of experience showed improved completion of procedural steps, higher Objective Structured Assessment of Technical Skills scores, and decreased force applied to tissue by the esophagoscope after the simulation exercise.…”
Section: Discussionmentioning
confidence: 99%